Comparative Benefit Value Analysis of Ecotourism and Masstourism in Malang Regency, East Java - Silvia Kusuma Intansari; Nuddin Harahab (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2018)
Demand for marine tourism is high today causing maritime tourism offered by the Government and coastal communities to increase. Development and development of tourism conducted to meet the public demand for marine tourism is required for the management of the achievement of community welfare. The required management must be balanced between ecological function and economic function. The purpose of this study is to know and analyze the involvement of the community, partners, visitation, amount of income, and ecological tourism development of CMC Three Colors and Coast of Goa of China. The research method used is qualitative descriptive analysis with interview and observation research technique. The results show that the comparison of the management of the two coastal tours can be seen from the involvement of the community and partners on tourism, the number of visits and the amount of income, and the development of the ecological function of the two tours. CMC Tour Three Colors that have the concept of ecotourism get other benefits higher than the disadvantages of the management performed. Ecological functions and economic functions can be balanced. While the Coast of Goa of China with the concept of masstourism get other benefits less than the loss of management because of the management focused on economic function so that other benefits to the ecological function of degradation.